2016
DOI: 10.1002/uog.15880
|View full text |Cite
|
Sign up to set email alerts
|

Ethics and social acceptability of a proposed clinical trial using maternal gene therapy to treat severe early‐onset fetal growth restriction

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 19 publications
(20 reference statements)
1
33
0
Order By: Relevance
“…In stakeholder and patient interviews conducted by the EVERREST consortium, a primary issue raised when considering a trial of maternal gene therapy for FGR, was the additional psychological distress that is added to an already stressful situation, through asking a pregnant woman to consider taking part in a trial (Table 2). Interestingly, maternal gene therapy was for the majority of stakeholders considered to be acceptable if there was clear fetal benefit (76). Likewise, most women felt they had the capacity to make informed decisions whilst pregnant, which aligns with the recommendations by the CIOMS (68), so long as they were provided with the information required to make an autonomous decision.…”
Section: Despite the 2002 Council For International Organizations Of mentioning
confidence: 83%
“…In stakeholder and patient interviews conducted by the EVERREST consortium, a primary issue raised when considering a trial of maternal gene therapy for FGR, was the additional psychological distress that is added to an already stressful situation, through asking a pregnant woman to consider taking part in a trial (Table 2). Interestingly, maternal gene therapy was for the majority of stakeholders considered to be acceptable if there was clear fetal benefit (76). Likewise, most women felt they had the capacity to make informed decisions whilst pregnant, which aligns with the recommendations by the CIOMS (68), so long as they were provided with the information required to make an autonomous decision.…”
Section: Despite the 2002 Council For International Organizations Of mentioning
confidence: 83%
“…A bioethical study found no absolute ethical, regulatory, or legal objections to the use of maternal gene therapy in pregnancy, with patients welcoming the development of new drugs for this untreatable disease. 92 The consortium is performing a prospective observational study of pregnancies with severe earlyonset FGR to define their trial inclusion criteria, which is likely to recruit those women who are most at risk of an intrauterine death or neonatal death between 22 and 27 weeks of gestation. 93 Nanotechnology and other uteroplacental targeting strategies to treat FGR There are a number of other novel strategies emerging that could target drugs or particles to the uteroplacental circulation and/or the trophoblast with the aim of improving uterine blood flow, placental function, or both (Table 3).…”
Section: Maternal Vegf Gene Therapymentioning
confidence: 99%
“…There is considerable personal, familial, and societal pressure on pregnant women to act selflessly for their unborn child; she may feel she ‘has no choice’ . When assessing a prenatal therapy, many pregnant women consider their fetus as a baby, even if they have not attained a ‘viable’ gestational age . As fetal intervention moves increasingly into the mainstream, placing safeguards to prevent diminution of maternal autonomy may protect mothers in the long run.…”
Section: The Legal Position On Fetal Interventionmentioning
confidence: 99%
“…46,47 When assessing a prenatal therapy, many pregnant women consider their fetus as a baby, even if they have not attained a 'viable' gestational age. 48 As fetal intervention moves increasingly into the mainstream, placing safeguards to prevent diminution of maternal autonomy may protect mothers in the long run. Furthermore, the fetus's lack of rights prevents its classification as a patient, so it is not supported by the personhood/patienthood structure.…”
Section: The United Kingdommentioning
confidence: 99%